Visiting Rose and Albert Watkins in Huntington Beach, CA - Watkins, Howard::::::::: (1980)
Howard Watkins, Adam Watkins, Albert Watkins holding California license plate "A 26T W" in front of family Model T Ford Adam standing on trailer's spare tire